FOSTERING POSITIVE DISCIPLINE AMONG SCHOOL STUDENTS EXPANDS EDUCATIONAL OPPORTUNITIES - Yusinchai, Yupin; Parchanban, Pakorn; Kornpuang, Anucha; Sawangmek, Taweesak (Journal of Education and Innovation, 2025)
Education is an important foundation for developing human resources and the nation, especially in an era where the world is rapidly changing in terms of technology, economy, and society. Therefore, providing quality and comprehensive education is essential. Thailand places importance on expanding educational opportunities by establishing schools for expanding educational opportunities so that students in remote or disadvantaged areas can receive continuous education up to lower secondary level. The management of these schools remains a challenge due to resource limitations and different social contexts. In addition, another important challenge for schools for expanding educational opportunities is instilling educational values that help students develop into individuals with desirable characteristics, especially discipline, which is an important foundation for learning and living. Discipline does not only mean following school rules and regulations, but also includes self-responsibility, learning patience, and effective time management. Students with discipline will be able to set educational goals, track their academic performance, and continuously strive for self-development. Positive Discipline is an approach that focuses on strengthening students’ good behavior without using harsh punishments, but rather emphasizing emotional support, providing clear guidelines, and using positive reinforcement. Therefore, the use of positive discipline is an important tool in developing behavior and creating an environment conducive to learning. The process of promoting positive discipline can be divided into 3 stages: the upstream stage, which is policy setting, teacher training, and creating a school culture that promotes good behavior; the midstream stage, which is the use of positive techniques such as giving praise, setting common rules, and behavioral enhancement activities; and the downstream stage, which is the monitoring of students’ behavior, providing counseling, and adjusting the approach to be appropriate. Evaluation uses behavioral observation, questionnaires, and quantitative data to examine the results. Applying the concept of positive discipline promotion in the context of an educational opportunity expansion school is important and challenging to help students develop appropriate behaviors, reduce conflicts in school, and create a learning atmosphere that promotes cooperation and responsibility among students. In the approach to promoting positive discipline, administrators should set policies that support teachers using positive reinforcement, and parents should promote good behavior at home. Positive discipline will help students participate in developing an understanding of their own behavior, learning from mistakes, and enhancing problem-solving skills. It also helps create a close and trusting relationship between students and teachers, which is an important factor in developing sustainable behavior and learning.